Odpowiedzi

2010-04-11T20:57:19+02:00
2 3/5x+3=5 2/3x-1/5
2 9/15x+3=5 10/15x-1/5
2 9/15-5 10/15x= -1/5 -3
-3 1/15x= - 3 1/5
- 46/15 x= - 16/5
x= -16/5: (-46/15)
x= -16/5*(- 15/46)
x= -8* (-3/23)
x= 24/23
x= 1 1/23



1 1/5x-2(1-1,5x)=7(4+3/5x)
1,2x-2+3x=7(4+0,6x)
1,2x-2+3x=28+4,2x
1,2x+3-4,2x= 28+2
0=30 (równanie nie ma rozwiązania)



0,3(5+10x)=1,5-2(4-3/4x)=
1,5+3x=1,5-2(4-0,75x)
1,5+3x=1,5-8+1,5x
3x-1,5x=1,5-8-1,5
1,5x= -8
x= -8:15/10
x= -8*10/15
x= -80/15
x= - 16/3
x= -5 1/3


x/12+5x/6+3x/4-1=5(x-1,2)
x/12 +10x/12 + 9x/12 -1 = 5x-6
20x/12-5x= -6+1
20x/12-60x/12= -5
-40x/12= -5 (obie strony mnożę przez 12)
-40x= -60
x= 60/40
x= 6/4
x= 1 2/4
x= 1 1/2



5[5(5-2x)-2x]-2x=2(2 1/2-x)
5[5(5-2x-2x)]-2x=2(2,5-x)
5(25-10x-10x)-2x=5-2x
125-50x-50x-2x=5-2x
-50x-50x-2x+2x= 5-125
-100x= -120
x= 120/100
x=1,2